PENGARUH PEMBELAJARAN E-LEARNING DAN KEBIASAAN BELAJAR TERHADAP PENINGKATAN KOMPETENSI MAHASISWA PASCASARJANA PADA UNIVERSITAS BINA NUSANTARA - Angelina Ervina Jeanette Egeten (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2017)
E-learning is a learning method that using electronic media as teaching materials to students. The definition of E-learning is very wide, which by terminology associated with online learning. Elearning in Bina Nusantara University is an E-learning which is done by online learning named as Binus Online Learning. Binus Online Learning applying the blended learning as a combination of online learning and face-to-face learning. The purpose of this study was to determine the effect of E-learning system and learning habits towards the online and regular students of MMSI and MTI major. Data were taken from 210 respondents of regular and online active student of Bina Nusantara University, and analyzed with the Pearson product moment parametric correlation using SPSS 21 as tools. Further research was conducted to compare the competence between regular and online class based on MMSI and MTI major using cross tabulation and one way ANOVA to significant difference test.